PENGEMBANGAN MEDIA PEMBELAJARAN E-BOOK BERBASIS FLIP PDF PROFESIONAL PADA KOMPETENSI NAIL ART DI SMKN 3 KOTA KEDIRI - Malayinin Ni'mah; Nia Kusstianti; Sri Dwiyanti; Novia Restu Windayani (Program Studi Pendidikan Tata Rias, 2025)
Flip PDF Professional as a learning media that can create a more interesting learning atmosphere. The purpose of the study was to determine the results of the development of learning media, the feasibility of learning media, learning outcomes, and student responses. The research method used was Research & Development (R&D). The results of the study showed that e-books were developed with limited define, design, develop, and dissaminate stages, e-book media can be accessed via links and barcodes, the result of the media feasibility test got an average percentage of 88% in the very feasible category, psychomotor learning outcomes got an average of 86> KKTP 80 which means complete, and student responses got an average percentage of 93% in the very good category. The results of the study showed that e-books based professional flip PDF were effective for learning.